2014
DOI: 10.1002/pip.2496
|View full text |Cite
|
Sign up to set email alerts
|

Back amorphous‐crystalline silicon heterojunction (BACH) photovoltaic device with facile‐grown oxide ‐ PECVD SiNx passivation

Abstract: This article reports on the integration of facile native oxide-based passivation of crystalline silicon surfaces within the back amorphous-crystalline silicon heterojunction solar cell concept. The new passivation scheme consists of 1-nm thick native oxide and nominally 70-nm thick PECVD silicon nitride. The low temperature passivation scheme provides uniform high quality surface passivation and low parasitic optical absorption. The interdigitated doped hydrogenated amorphous silicon layers were deposited on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…One of the key challenges in general for large-scale production of back-contacted solar cells lies in developing cost-effective technologies for forming the amorphous/crystalline heterocontacts which lie side by side on the back side of the cell. Standard photolithography, which is commonly used in laboratory devices for patterning of both emitter [9] and metallization layers [10], clearly is too costly for integration in production processes. While for metallization industry-proven screen printing techniques are in principle available, there is still a need for the development of a cost-effective and reliable heterocontact patterning technology for SHJ solar cells.…”
mentioning
confidence: 99%
“…One of the key challenges in general for large-scale production of back-contacted solar cells lies in developing cost-effective technologies for forming the amorphous/crystalline heterocontacts which lie side by side on the back side of the cell. Standard photolithography, which is commonly used in laboratory devices for patterning of both emitter [9] and metallization layers [10], clearly is too costly for integration in production processes. While for metallization industry-proven screen printing techniques are in principle available, there is still a need for the development of a cost-effective and reliable heterocontact patterning technology for SHJ solar cells.…”
mentioning
confidence: 99%
“…Moreover, a systematic study of the cell performance on cell design parameters has recently been demonstrated for Back Amorphous-Crystalline silicon Heterojunction solar cell using this native oxide based passivation scheme. 12 In this article, we report an alternative heterojunction cell concept, the Laterally Inherently Thin (LIT) amorphouscrystalline silicon PV device, which offers the potential of attaining enhanced current density in contrast to the HIT cell concept. The LIT cell concept requires high quality passivation of the silicon surface as well as optical transparency of the passivation layers.…”
mentioning
confidence: 99%
“…The facile grown native oxide for this set of experiments was grown in a controlled clean-room ambient at room temperature for a defined period. 11,12 Alternative low temperature grown oxides using nitric acid, ozone ambient in atmospheric or aqueous media, and piranha can also be used for passivation. 11 Following the growth of the facile native oxide layer, 45 nm thick SiN x layer was deposited on the front surface of cSi wafer using the Oxford Plasmalab 100 PECVD system.…”
mentioning
confidence: 99%